Psychological Well-Being Mediates Cyberbullying Victimization and Risky Health Behavior: Public Health Implications for Universities - Purwo Setiyo Nugroho; Bhubate Samutachak; Tawanchai Jirapramukpitak; Fatimah Ahmad Fauzi; Ghozali Ghozali; Aphichat Chamratrithirong (Journal of Public Health and Pharmacy, 2025)
Introduction: Cyberbullying has become a burden in the current digital world and has an impact on health status, including physical and mental health. People try to mitigate these mental health issues through various coping strategies, including engaging in risky health behavior. Such risky health behaviors may have implications for future health status.  Thus, this study aims to examine the prevalence of cyberbullying victimization and elucidate the consequences of cyberbullying victimization on psychological well-being and risky health behavior.